2013
DOI: 10.1021/la401556k
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Size Effects on Cell Interaction of Gold Nanoparticles with Both Phagocytic and Nonphagocytic Cells

Abstract: With the development of nanotechnology and its application in biomedicine, studies on the interaction between nanoparticles and cells have become increasingly important. To understand the surface and size effects on cell interaction of nanoparticles, the cellular uptake behaviors of two series of gold nanoparticles (AuNPs) with both positively and negatively charged surfaces and sizes range from ~16 to ~58 nm were investigated in both phagocytic RAW 264.7 and nonphagocytic HepG2 cells. The internalization of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 59 publications
6
150
0
Order By: Relevance
“…This result is different from previous data where negatively charged AuNP-MUA NP decreased cellular dehydrogenase levels on RAW 264.7 phagocytes and relatively small NPs (16 nm) revealed higher toxicity than large particles. 35 Thus, we conclude that the biocompatibility of GNPs depends not only on surface functionalization but also on the tested cell line and cell types. In agreement with data from Taylor et al who found that multiple NP properties such as size, zeta potential, and surface functionalization can determine their toxic effects on cells, 46 we conclude that AuroVist™ GNPs are nontoxic to murine macrophages, but these data may not be transferred to other GNPs exhibiting similar size or zeta potential.…”
Section: Domey Et Almentioning
confidence: 71%
See 3 more Smart Citations
“…This result is different from previous data where negatively charged AuNP-MUA NP decreased cellular dehydrogenase levels on RAW 264.7 phagocytes and relatively small NPs (16 nm) revealed higher toxicity than large particles. 35 Thus, we conclude that the biocompatibility of GNPs depends not only on surface functionalization but also on the tested cell line and cell types. In agreement with data from Taylor et al who found that multiple NP properties such as size, zeta potential, and surface functionalization can determine their toxic effects on cells, 46 we conclude that AuroVist™ GNPs are nontoxic to murine macrophages, but these data may not be transferred to other GNPs exhibiting similar size or zeta potential.…”
Section: Domey Et Almentioning
confidence: 71%
“…52 The authors concluded that these GNPs efficiently accumulate within these cells due to opsonization. In addition, it was shown before that NPs with a higher diameter (~40 nm) and negatively charged GNPs were taken up by phagocytes in advance to positively charged or smaller NPs, 35 demonstrating that AuroVist™ 15 nm with a hydrodynamic diameter of 36 nm and a negative zeta potential might behave similarly. Consequently, it is most likely that the mCT signals of edema occur to an extent due to the uptake of negatively charged 15 nm AuroVist™ NPs into phagocytic cells from the blood stream subsequently migrating to the edema region.…”
Section: Domey Et Almentioning
confidence: 89%
See 2 more Smart Citations
“…However, as shown in the study by Petri-Fink et al (2005), due to the interaction of the amino groups on the surface of CS with the negatively charged domains on cell membranes, CS-IONPs pass through the cell membrane. Cationic NPs were shown to have enhanced cellular uptake compared to anionic or neutral NPs and to induce more ROS and mitochondrial and lysosomal damage (Mahmoudi et al, 2011a;Liu et al, 2013;Calatayud et al, 2014). They were also shown to cause more disruption of plasma membrane integrity and more hole formation, particularly in nonphagocytic cells (Nafee et al, 2009;Frohlich, 2012;Carvalho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%